2020
DOI: 10.3390/f11050492
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical Processes of C and N in the Soil of Mangrove Forest Ecosystems

Abstract: The mangrove forest provides various ecosystem services in tropical and subtropical regions. Many of these services are driven by the biogeochemical cycles of C and N, and soil is the major reservoir for these chemical elements. These cycles may be influenced by the changing climate. The high plant biomass in mangrove forests makes these forests an important sink for blue C storage. However, anaerobic soil conditions may also turn mangrove forests into an environmentally detrimental producer of greenhouse gase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 135 publications
2
22
0
1
Order By: Relevance
“…Microorganisms (here meaning single-celled members of the domains bacteria, archaea, and eukarya) are a key component of the mangrove forest and are present in the sediment, the water column, and as biofilms on mangrove roots ( Vazquez et al., 2000 ; Holguin et al., 2001 ). These microbes interact with mangroves as co-dependent ecosystem engineers and are responsible for many of the biogeochemical processes attributed to mangrove forests ( Holguin et al., 2006 ; Reis et al., 2017 ; Shiau and Chiu, 2020 ). Mangrove forest productivity, for example, is dependent on the microbial recycling mechanisms that keep nitrogen and other nutrients within the system ( Alongi, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms (here meaning single-celled members of the domains bacteria, archaea, and eukarya) are a key component of the mangrove forest and are present in the sediment, the water column, and as biofilms on mangrove roots ( Vazquez et al., 2000 ; Holguin et al., 2001 ). These microbes interact with mangroves as co-dependent ecosystem engineers and are responsible for many of the biogeochemical processes attributed to mangrove forests ( Holguin et al., 2006 ; Reis et al., 2017 ; Shiau and Chiu, 2020 ). Mangrove forest productivity, for example, is dependent on the microbial recycling mechanisms that keep nitrogen and other nutrients within the system ( Alongi, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that other environmental variables such as granulometry, vegetation, and pollutant distributions may also impact mangrove sediment communities, as observed previously (Peixoto et al, 2011;Colares and Melo, 2013;Rocha et al, 2016). Furthermore, it is also possible that they are influenced by additional biological factors, such as fungi and other eukaryotic microbes (Simões et al, 2015), and plant rhizome contamination (Bennett and Klironomos, 2019;Miller et al, 2019), as observed in previous work (Rocha et al, 2016;Zhang et al, 2017). Thus, our understanding of prokaryotic community structures will be greatly increased if complemented with rhizome and eukaryotic population information.…”
Section: Discussionmentioning
confidence: 64%
“…On the other hand, the global warming-induced salt water intrusions in coastal ecosystems may also increase the salinity by 1–3 psu [ 43 ], which likely increases the Type Ia methanotrophic population and methane uptake capacity. Moreover, the competitions between sulfate reducing bacteria and methanogens for C sources may also shift under increased SO 4 2- due to global warming [ 42 , 44 ]. All of these factors likely reduce the overall CH 4 flux and increase CO 2 flux from mangrove ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Climate change and warming global temperatures appear to increase litter decomposition in mangrove forests [41], which likely accelerates the C cycle in and increase greenhouse gas emissions from mangrove soils [42]. On the other hand, the global warming-induced salt water intrusions in coastal ecosystems may also increase the salinity by 1-3 psu [43], which likely increases the Type Ia methanotrophic population and methane uptake capacity.…”
Section: Composition and Adaptation Of Methanotrophs In Field Mangrovmentioning
confidence: 99%
See 1 more Smart Citation